HIGH PERFORMANCE EDUCATION: CONTEXTS. OBJECTIVES. STRATEGIES - Mitrofan CIOBAN (Academy of Sciences of Moldova, 2014)
In the article, pedagogical concepts regarding the differentiated and individualized approach to the educational process with the goal of achieving high performances are analyzed. The evolution of these concepts is refl ected in a historical aspect in terms of the current contexts of the autochthonous educational system. Some conclusions and recommendations regarding the support of disciplines from the fi elds of Exact and Natural Sciences at all stages and levels of education are formulated. The necessity of initial professional formation of the didactic staff for activities with students capable of high results is argued.